PENGALAMAN PERAWAT DALAM PENANGANAN CARDIAC ARREST DI INSTALASI GAWAT DARURAT RSUP PROF. Dr. R. D. KANDOU MANADO - Ismiroja, Rahmat; Mulyadi, Ns.; Kiling, Maykel (JURNAL KEPERAWATAN, 2018)
Abstract : Sudden cardiac death is a dysfunction of the heart's electricity and produces abnormal heart rhythms. Report data at the Emergency Room of RSUP Prof. Dr. R.D Kandou Manado during the months of January to September 2017 there were 574 patients experiencing cardiac arrest and who died as many as 438 patients with obstacles due to limited space full of health workers and fa-cilities. The purpose of the study was to determine the experience of nurses in handling cardiac ar-rest at the Emergency Room of the RSUP Prof. Dr. R D Kandou Manado. This study uses a phe-nomenological qualitative design. The sampling technique was purposive sampling involving 4 participants. Data collection is done with in-depth interviewing. The analysis technique used is the Colaizzi method. The results of the study of 1) knowledge obtained the theme (a) physical assess-ment (b) physiological assessment. 2) action obtained theme (a) check pulse, (b) check response. 3) supporting factors are found in the theme of (a) the condition and general condition of the patient, (b) the skills and abilities of the officers, (c) the response of the officers and facilities. 4) the inhibit-ing factor is the theme of (a) human resources, (b) the skills of officers and infrastructure. The con-clusion in this study that the experience of nurses in handling cardiac arrest is supported by the knowledge and readiness of nurses with facilities and infrastructure barriers. Keywords: Experience, Nurse, Handling, Cardiac Arrest Abstrak : Kematian jantung mendadak merupakan tidak berfungsinya kelistrikan jantung dan menghasilkan irama jantung yang tidak normal. Data laporan di Instalasi Gawat Darurat RSUP Prof Dr. R.D Kandou Manado selama bulan Januari sampai September 2017 terdapat 574 pasien mengalami cardiac arrest dan yang meninggal dunia sebanyak 438 pasien dengan hambatan karena keterbatasan tempat penuh sehingga kekurangan tenaga kesehatan dan fasilitas. Tujuan penelitian untuk mengetahui pengalaman perawat dalam penanganan cardiac arrest di Instalasi Gawat Darurat RSUP Prof Dr R D Kandou Manado. Penelitian ini menggunakan rancangan kuali-tatif fenomenologis. Teknik pengambilan sampel dengan purposive sampling yang melibatkan 4 partisipan. Pengumpulan data dilakukan dengan in-depth interviewing. Teknik analisa yang digunakan adalah metode Colaizzi. Hasil penelitian dari 1) pengetuahuan didapatkan tema (a) penilaian secara fisik (b) penilaian secara fisiologis. 2) tindakan didapatkan tema (a) cek nadi, (b) cek respon. 3) faktor pendukung didapatkan tema (a) kondisi dan keadaan umum pasien, (b) skill dan kemampuan petugas, (c) respon petugas dan sarana prasarana. 4) faktor penghambat didapatkan tema (a) Sumber daya manusia, (b) skill petugas dan sarana prasarana. Kesimpulan dalam penelitian ini bahwa pengalaman perawat dalam penanganan cardiac arrest didukung oleh penge-tahuan dan kesiapan perawat dengan hambatan sarana dan prasarana. Kata kunci : Pengalaman, Perawat, Penanganan, Cardiac Arrest